Hinduism in the Internet Age: a psychological anthropological study of cultural collisions and Rajasthani emerging adults' well-being - Else, Robert James, author; Snodgrass, Jeffrey G., advisor; Browne, Katherine E., committee member; MacKenzie, Matthew, committee member (Colorado State University. Libraries, 2017)
As the world globalizes at an ever quickening pace, it becomes increasingly important to understand the ways in which potentially competing cultural ideas come into contact with one another, alongside the possible repercussions of such interactions. This research looks at a particular example of this in the Indian city of Udaipur, Rajasthan via an ethnographic field study of Hindu university students' views on Hindu religious traditions and what it means to be a "good Hindu" in modern India, as well as how religious ideas intersect with valuations of the internet in a rapidly globalizing nation. A psychological anthropological perspective, and specifically a cognitive anthropological "cultural models" or "mental representations" approach, allows for the identification of culture-specific understandings of Hinduism and the internet, as well as how these understandings interact with one another to both form identity and impact stress and subjective well-being among emerging adults. Relying on both qualitative and quantitative data analysis, the relationship between religiously- and technologically-informed models is found to be either competing, complementary, or independent. While the majority of Hindu university students in Udaipur don't consider these two models to be at odds with one another, this research suggests that for those Hindu university students who consider these models to be competing, there is a statistically significant increase in self-reported stress.
Keywords: globalization; identity; psychological anthropology; cultural models; India; Hinduism